Characterization of Paediatric Prurigo Nodularis: A Multicentre Retrospective, Observational Study - Rotem Kyvayko; Tahel Fachler-Sharp; Shoshana Greenberger; Amir Horev; Vered Molho-Pessach (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)